Method for preparing solar cell through dual-band absorption and solar cell
By using the dual-band absorption technology of TPD-2TPA and Y6 small molecule materials, combined with solvent vapor treatment and annealing technology, the poor balance of PCE and AVT in high-transparent solar cells is solved, and efficient photoelectric conversion and high AVT solar energy are achieved. Battery, reduces costs and improves stability.
Patent Information
- Application Number
- CN202310831784.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
When the average visible light transmittance (AVT) exceeds 70%, the photoelectric conversion efficiency (PCE) of existing high-transparent solar cells decreases sharply, and the dual-band absorption technology is complex and costly, and the material stability is poor, making it difficult to achieve balanced PCE and AVT. .
TPD-2TPA and Y6 are used as small molecule active materials to form a light-absorbing active layer through surfactant and diluent treatment. Combined with solvent steam treatment and annealing technology, a dual-band absorbing solar cell can absorb both ultraviolet and near-infrared light is prepared. Avoid visible light areas and improve photoelectric conversion efficiency.
It achieves efficient photoelectric conversion efficiency and high AVT balance, reduces preparation costs, simplifies the material purification process, improves the stability and transparency of the device, and broadens the application fields.
Smart Images

Figure CN119277940A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic devices, and in particular to a method for preparing a solar cell using a dual-band absorption strategy, and a solar cell prepared thereby. Background Art
[0002] Solar cells are electrochemical devices that convert light energy into electrical energy. In the solar spectrum, in addition to the visible light region, the number of ultraviolet photons is limited, and the theoretical photoelectric conversion efficiency of the corresponding device is less than 7%. In addition, more than half of the solar energy is distributed in the near-infrared region. Therefore, photovoltaic devices that effectively utilize sunlight in the ultraviolet and near-infrared regions can achieve higher efficiency.
[0003] Transparent solar cells are a promising photovoltaic technology that can be used in integrated photovoltaic systems in buildings, greenhouses and other fields without compromising their aesthetics. An ideal transparent photovoltaic (TPV) device should mainly absorb ultraviolet (UV) and near-infrared (NIR) light, allowing visible light to pass through. In addition, the device also needs to produce high photocurrent and photoelectric conversion efficiency (PCE). Reducing visible light absorption will significantly reduce the device photocurrent and PCE, so it is crucial to balance the PCE and average visible light transmittance (AVT) of the device. To maintain a high PCE, most research has focused on semi-transparent solar cells (AVT < 50%), but highly transparent solar cells (AVT > 50%), especially AVT > 70%, have important applications in the actual construction industry and other special occasions. For TPV devices, a notable challenge is that the PCE drops sharply when the AVT exceeds 60%. So far, TPVs with AVT exceeding 70% mainly use active layer materials with full UV or full NIR absorption. Devices with dual-band absorption have high requirements on the absorption edge and photovoltaic performance of the material.
[0004] The current highly transparent solar cells, especially TPV devices with an AVT of more than 70%, use active layers that are mainly materials that absorb in the entire ultraviolet region or the entire near-infrared region, and the overall utilization rate of the solar spectrum is low. For example, Document 1 "Lead Halide Ultraviolet-Harvesting Transparent Photovoltaics with an Efficiency Exceeding 1%" (Dianyi Liu et al., ACS Appl. Energy Mater. 2019, 2, 3972-3978) uses materials that absorb in the entire ultraviolet region, and the final device achieves an AVT of 70.7% and a PCE of 1.22%. Document 2 "Design of UV-Absorbing Donor Molecules for Nearly Imperceptible Organic Solar Cells" (Melissa L. Ball et al., ACS Energy Lett. 2022, 7, 180-188) uses ultraviolet absorbing materials, and the prepared TPV device has an AVT of 80.3%-82.0% and a PCE of 0.43-0.70%.
[0005] In other prior art transparent solar cells, polymer materials are often used as active layers, which have poor batch stability and complex synthesis compared to small molecule materials. For example, document 3 "Balancing efficiency and transparency in organic transparent photovoltaics" (Ruiqian Meng et al., npj Flexible Electronics (2022) 6: 39) uses near-infrared absorbing PTB7-Th:IEICO-4F as an active layer material. When the device AVT exceeds 70% and 80% respectively, the corresponding device PCE can reach 4.06% and 2.38%.
[0006] There are few dual-band absorption transparent solar cells reported so far. Document 4 "Vacuum-deposited Transparent Organic Photovoltaics for Efficiently Harvesting Selective Ultraviolet and Near-Infrared Solar Energy" (Meng-Zhen Li et al., Sol. RRL 2021, 5 (3), 2000564) discloses the realization of dual-band absorption in highly transparent solar cells with an AVT greater than 70%, but uses near-infrared absorption materials as donors and ultraviolet absorption materials as acceptors. And this group of active layer materials all need to be deposited by evaporation, which increases the cost of application. In order to achieve an AVT of greater than 70% for the entire device, the electrode used in this work is also a evaporated Cu: Ag / WO3 composite electrode, which requires precise control of the proportion of materials in the electrode. In addition, the PCE achieved by the device is only 1.34%.
[0007] Document 5 "Highly Efficient Semitransparent Solar Cells with Selective Absorption and Tandem Architecture" (Lijian Zuo et al., Adv. Mater. 2019, 1901683) also discloses a method for preparing solar cells using dual-band absorption. 2.43 Cl 0.57 PTB7-Th:6TIC-4F and PTB7-Th:6TIC-4F were used to absorb UV and NIR light, respectively, to construct a device with a PCE of 10.7% and an AVT of 52.91%. However, the process of using a stacked device increased the complexity of device preparation and the application cost. Moreover, it was used in transparent solar cells with an AVT of less than 70% but higher than 50%.
[0008] Therefore, there remains a continuing need to prepare solar cells with balanced PCE and average visible transmittance (AVT). Summary of the invention
[0009] Therefore, an object of the present invention is to provide a method for preparing a solar cell by dual-band absorption, thereby making full use of the energy of sunlight in the ultraviolet and near-infrared regions.
[0010] Another object of the present invention is to provide a solar cell prepared by the above method.
[0011] According to one embodiment of the present invention, a method for preparing a solar cell with dual-band absorption is provided, the method comprising the following steps:
[0012] S1) ultrasonically cleaning the conductive bottom electrode with a surfactant and a detergent respectively to obtain a treated bottom electrode layer;
[0013] S2) diluting the hole transport material with a diluent, spin coating the material on the bottom electrode layer treated in step S1), and then annealing the material to form a hole transport layer on the bottom electrode layer treated;
[0014] S3) dissolving the first active material and the second active material in a first solvent, spin coating the materials on the hole transport layer in step S2), and then annealing the materials at 50-200° C. or treating the materials with the second solvent vapor at 20-50° C., thereby further preparing a light absorbing active layer on the product of step S2);
[0015] The first active material is a small molecule having an absorption cutoff wavelength below 600 nm, and the second active material is a small molecule material having absorption in the near infrared region, and its absorption wavelength can be up to 800 nm-1500 nm;
[0016] The solvent vapor treatment includes adding a second solvent into a glass culture dish until the vapor is saturated, then placing the spin-coated active layer film on the back of another blank culture dish cover, and quickly exchanging the culture dish cover on which the active layer film is placed with the culture dish cover containing the saturated vapor of the second solvent, for 0 seconds to 300 seconds, preferably 1 to 300 seconds, and more preferably 10 to 120 seconds, and then taking out the film from the culture dish to obtain a light-absorbing active layer;
[0017] S4) spin coating an electron transport material on the product of step S3), thereby further preparing an electron transport layer on the product of step S3);
[0018] S5) Using PDMS, the top electrode is transferred onto the electron transport layer obtained in step S4) to produce a solar cell.
[0019] The surfactant is a conventional surfactant known in the art for washing.
[0020] The detergent is a reagent known in the art for washing, for example, deionized water, ethanol, isopropanol or a mixture thereof, preferably deionized water and isopropanol.
[0021] The diluent is a dilution agent known in the art, including, for example, ethanol and water.
[0022] According to one embodiment of the present invention, the bottom electrode is selected from an ITO bottom electrode, a FTO bottom electrode, an AZO bottom electrode, AgNW or a carbon electrode.
[0023] According to one embodiment of the present invention, the hole transport material is selected from one or more mixed materials of PEDOT:PSS, MoO3, CuI, CuPc, ZnPc, TiOPc, PF8-TAA, PIF8-PTAA, PTAA, PTB7, Alq3, CuSCN, PFO, CuInS2, NiOx, WOx, and Spiro-OMeTAD.
[0024] According to one embodiment of the present invention, the first active material is TPD-2TPA, and the second active material is Y6.
[0025] The active layer material TPD-2TPA has a cutoff absorption wavelength of 500nm and a band gap of 2.48eV. It mainly absorbs light in the ultraviolet region. The absorption wavelength of Y6 can reach 1000nm, and it mainly absorbs light in the near-infrared region. By combining the two materials, the active layer film can absorb ultraviolet and near-infrared light at the same time. When preparing transparent photovoltaic cells, it can avoid the visible light region of the human eye's visual response. Ultimately, when improving the AVT of the device, it improves the utilization of the spectrum and improves the photoelectric conversion efficiency of the device.
[0026] Moreover, the active layer material used is a device made of all small molecules, which has low preparation cost, simple purification method, clear molecular weight of the material, good batch stability of the material and stability of the final device. Moreover, the active layer using all small molecule materials for dual-band absorption effectively avoids the strong spectral corresponding area of the human eye.
[0027] The active layer film uses a bulk heterojunction structure. Compared with stacked cells, the device structure is simple and easy to manufacture.
[0028] Since the active layer film can obtain photovoltaic films with good performance under room temperature solvent vapor treatment and annealing conditions, the device process can be used to construct rigid devices as well as to prepare flexible devices, thus broadening the application field.
[0029] According to one embodiment of the present invention, the first solvent used in step S3) is selected from chloroform, CB, and toluene; the second solvent is selected from chloroform, THF, CB, CS2 and toluene; the concentration of the first solvent is 10-25 mg / mL; the concentration of the second solvent is such that it is vapor saturated in the culture dish; the mass ratio of the first active material to the second active material is 1:4 to 4:1; the annealing temperature is 130-150°C; and an active layer additive is optionally further added, the active layer additive being 0.5%-3% by volume of chloronaphthalene.
[0030] According to one embodiment of the present invention, the electron transport material is selected from one or more of PDINO, BCP, ZnO, MgO, SnO2, TiO2, ZrO2, Nb2O3, Al2O3, PEIE, PFN-Br, PFSO3Na, PFN / PFBT, and Alq3.
[0031] According to one embodiment of the present invention, the positions of the electron transport layer and the hole transport layer can be interchanged.
[0032] According to one embodiment of the present invention, the top electrode is selected from one or more mixed materials of PH1000:AgNWs, PH1000, AgNWs, CuNWs, ITO, carbon nanotubes, graphene, etc.
[0033] According to one embodiment of the present invention, the step S5) is performed in the following manner: AgNWs are added to a PH1000 solution to form a mixed solution, which is then spin-coated on PDMS after mixing, and the PDMS spin-coated with PH1000:AgNWs is inverted and pressed on the electron transport layer obtained in step S4); the PDMS is removed to make a solar cell.
[0034] Therefore, the PH1000:Ag NWs electrode can be prepared at room temperature, reducing the cost of production. In addition, the material ratio in the electrode does not need to be precisely controlled.
[0035] According to one embodiment of the present invention, the solar cell is an opaque or transparent solar cell.
[0036] According to one embodiment of the present invention, the solar cell is a flexible transparent solar cell.
[0037] According to one embodiment of the present invention, the method specifically comprises:
[0038] S11) ultrasonically cleaning the ITO substrate with a surfactant, deionized water and isopropyl alcohol respectively to obtain an ITO bottom electrode layer;
[0039] S12) diluting 4083 with a solvent such as ethanol or water, spin coating the 4083 on the cleaned ITO substrate at 4000 rpm, and then annealing at 150° C. for 10 min to obtain a PEDOT:PSS (4083) hole transport layer;
[0040] S13) TPD-2TPA and Y6 were dissolved in chloroform solvent and spin-coated on a 4083 substrate at 2000 rpm. The active layer conditions used in the device with the highest efficiency were a total concentration of 18 mg / mL, a mass ratio of donor to acceptor of 1:1, and no additives were added; and an annealing treatment or solvent vapor treatment was used to prepare a light-absorbing active layer;
[0041] The annealing treatment includes placing the active layer film obtained after spin coating on a hot stage at 140° C. for annealing treatment to obtain a light-absorbing active layer;
[0042] The solvent vapor treatment includes adding chloroform (2 mL) into a glass Petri dish at room temperature, closing the Petri dish for 5 minutes to saturate with vapor, placing the spin-coated active layer film on the back of another blank Petri dish lid, and quickly exchanging the lid with the Petri dish lid containing chloroform for 30 seconds, and then removing the film from the Petri dish to obtain a light-absorbing active layer;
[0043] S14) spin coating PDINO on the active layer at 3000 rpm to obtain a PDINO electron transport layer;
[0044] S15) Ag (60nm) to obtain an opaque solar cell; or
[0045] Using a PH1000:Ag NWs electrode prepared at room temperature, AgNWs were added to a PH1000 solution to form a mixed solution, which was then spin-coated on PDMS. The PDMS spin-coated with PH1000:AgNWs was inverted and pressed onto the device in front of the obtained transfer electrode; the PDMS was removed to obtain a transparent solar cell.
[0046] According to one embodiment of the present invention, a solar cell prepared according to the above preparation method is provided.
[0047] Beneficial Effects
[0048] The two active layer materials used in the present invention can absorb light in the ultraviolet region and near-infrared region, and avoid the visible light region to which the human eye responds, thereby improving the photoelectric conversion efficiency of the device by utilizing non-visible light. In addition, when a high-efficiency solar cell is prepared, the average visible light transmittance of the cell can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 is the molecular structure of the active material used according to an embodiment of the present invention.
[0050] Figure 2 FIG. 4 is a dual-band absorption spectrum of the active material used according to an embodiment of the present invention.
[0051] Figure 3 1 is a graph showing the morphological changes of the active layer film used according to an embodiment of the present invention after solvent vapor treatment (SVA), wherein a is a SEM image and b is an AFM image.
[0052] Figure 4 FIG. 4 is a statistical diagram of carrier mobility after treatment with solvent vapor according to an embodiment of the present invention.
[0053] Figure 5 FIG. 4 is a JV curve diagram of an opaque device under different annealing conditions according to an embodiment of the present invention.
[0054] Figure 6 FIG. 4 is a JV curve diagram of an opaque device at different donor-acceptor ratios (D:A) according to an embodiment of the present invention.
[0055] Figure 7 FIG. 4 is a graph showing JV curves of an opaque device with different concentrations of CN additives according to an embodiment of the present invention.
[0056] Figure 8 Schematic diagram of the structure of a high-transparency device according to an embodiment of the present invention.
[0057] Fig. 9 FIG. 4 is a JV curve graph of a transparent device having an AVT of 71.5% according to an embodiment of the present invention.
[0058] Fig.10 Spectrum of optical properties of a transparent device having an AVT of 71.5% according to an embodiment of the present invention.
[0059] Fig.11 Spectra of optical properties of samples before and after transferring the transparent top electrode according to an embodiment of the present invention (the device AVT is 71.5%).
[0060] Fig.12 FIG. 5 is a JV curve diagram of a flexible transparent device having an AVT of 70.6% according to an embodiment of the present invention. DETAILED DESCRIPTION
[0061] Example
[0062] The present invention will be further described below by way of examples, but the following examples are for illustrative purposes only and are not intended to limit the present invention.
[0063] Example 1: Preparation of an opaque solar cell
[0064] Preparation of ITO bottom electrode layer: The ITO substrate was ultrasonically cleaned with surfactant, deionized water and isopropyl alcohol respectively.
[0065] Preparation of PEDOT:PSS (4083) hole transport layer: 4083 was diluted with solvents such as ethanol or water, spin-coated on the cleaned ITO substrate at 4000 rpm, and then annealed at 150°C for 10 min.
[0066] Preparation of light-absorbing active layer: TPD-2TPA and Y6 were dissolved in chloroform solvent with a total concentration of 18 mg / mL, and the mass ratio of donor TPD-2TPA and acceptor Y6 was 1:1, and spin-coated on 4083 substrate at 2000 rpm. Annealing temperature was 140 °C, and no additives were added.
[0067] The molecular structures of active layer materials TPD-2TPA and Y6 are as follows Figure 1 The dual-band absorption spectrum of this material is shown in Figure 2 shown.
[0068] Preparation of PDINO electron transport layer: PDINO was spin-coated on the active layer at 3000 rpm.
[0069] Preparation of top electrode layer: For opaque solar cells, Ag (60nm) is used. The speed is deposited on the top.
[0070] As a result, the PCE of this solar cell can reach 7.34%.
[0071] Example 2-6: Preparation of solar cells under solvent vapor treatment
[0072] A solar cell was prepared in the same manner as in Example 1, except that a solvent vapor treatment was used instead of an annealing treatment in the preparation of the light absorbing active layer.
[0073] The solvent vapor treatment is specifically as follows: chloroform (2 mL) is added to a glass culture dish at room temperature, and the culture dish is closed for 5 minutes to saturate with vapor, the spin-coated active layer film is placed on the back of another blank culture dish cover, and the cover is quickly exchanged with the culture dish cover containing chloroform, and Examples 2-6 are respectively continued for 0 seconds, 10 seconds, 30 seconds, 60 seconds, and 120 seconds, after which the film is removed from the culture dish to obtain a light-absorbing active layer;
[0074] The AFM and SEM morphologies of the active layers obtained by solvent vapor treatment at room temperature for different times are shown in Figure 3 As shown, the roughness of the film treated with solvent vapor (SVA) is significantly increased.
[0075] The statistics of hole and electron mobility of the device after different time of solvent vapor treatment at room temperature are shown in Figure 2. Figure 4 As shown. Figure 4It can be seen that when the treatment is 30 seconds, the hole and electron mobility values of the device are closer, which is more conducive to the transfer of carriers and reduces the recombination of carriers.
[0076] Examples 7-11: Preparation of solar cells at different annealing temperatures
[0077] A solar cell was prepared in the same manner as in Example 1, except that the light absorbing active layer was annealed at 110° C., 120° C., 130° C., 140° C., and 150° C., respectively.
[0078] The JV curves of the opaque solar cells under different annealing conditions in Examples 1 and 7-11 are shown in FIG. Figure 5 shown.
[0079] Examples 12-16: Preparation of solar cells with different donor-acceptor ratios
[0080] A solar cell was prepared in the same manner as in Example 1, except that the donor and the acceptor were provided in ratios of 2:1, 1.5:1, 1:1.5, 1:2, and 1:4, respectively, when preparing the light absorbing active layer.
[0081] The JV curves of the opaque solar cells under different donor-acceptor ratios in Examples 1 and 12-16 are shown in FIG. Figure 6 shown.
[0082] Examples 17-18: Preparation of solar cells with different concentrations of additives
[0083] Solar cells were prepared in the same manner as in Example 1, except that the chloronaphthalene additives were added at volume ratios of 0.5% and 1%, respectively, when preparing the light absorbing active layer.
[0084] The JV curves of the opaque solar cells at different concentrations of additives in Examples 1 and 17-18 are shown in FIG. Figure 7 shown.
[0085] from Figure 5-Figure 7 The JV curve shows that by changing the conditions of annealing, DA ratio and additives, the optimal preparation conditions of the device active layer were finally screened out. Annealing at 140℃, DA ratio of 1:1, and no chloronaphthalene additive was added.
[0086] Example 19: Preparation of transparent solar cells
[0087] The structure of transparent solar cells is as follows Figure 8 shown.
[0088] Preparation of ITO bottom electrode layer: The ITO substrate was ultrasonically cleaned with surfactant, deionized water and isopropyl alcohol respectively.
[0089] Preparation of PEDOT:PSS (4083) hole transport layer: 4083 was diluted with solvents such as ethanol or water, spin-coated on the cleaned ITO substrate at 4000 rpm, and then annealed at 150°C for 10 min.
[0090] Preparation of light-absorbing active layer: TPD-2TPA and Y6 were dissolved in chloroform solvent and treated with solvent vapor. Chloroform (2 mL) was added to a glass culture dish and the dish was closed for 5 minutes to saturate the vapor. The film was placed on the back of another blank culture dish lid and the lid was quickly exchanged with the culture dish lid containing chloroform. After a duration of 30 s, the film was removed from the culture dish.
[0091] Preparation of PDINO electron transport layer: PDINO was spin-coated on the active layer at 3000 rpm.
[0092] Top electrode layer: Add AgNWs to the PH1000 solution to form a mixed solution, and after mixing, spin-coat it on the PDMS. Invert the PDMS spin-coated with PH1000:AgNWs and press it on the device in front of the obtained transfer electrode; remove the PDMS to complete the preparation of the transparent solar cell.
[0093] As a result, the AVT of the prepared transparent solar cell reached 71.5%, and the PCE reached 3.3%.
[0094] The JV curve of the high transparency solar cell is shown in Fig. 9 The optical properties spectrum is shown in Fig.10 The optical properties of the samples before and after the transparent top electrode transfer are shown in Fig.11 As shown. Figure 9-11 It can be seen that both sides of the device are highly transparent electrodes, and good photoelectric conversion efficiency can be obtained by irradiating the device from both sides. In addition, the optical performance and photocurrent results of the device can meet the optical consistency test. Since the AVT of the top transparent electrode used exceeds 85%, there is no obvious change in the AVT of the sample before and after the transfer electrode.
[0095] Example 20: Preparation of flexible transparent solar cells
[0096] A flexible transparent solar cell was prepared in the same manner as in Example 19, except that the bottom electrode layer was replaced with flexible PET / ITO instead of rigid ITO.
[0097] The JV curve of the flexible transparent solar cell is shown in Fig.12 As shown. Fig.12 It can be seen that flexible transparent solar cells with good performance can be prepared under room temperature treatment.
Claims
1. A method for preparing a solar cell by dual-band absorption, the method comprising the following steps: S1) ultrasonically cleaning the conductive bottom electrode with a surfactant and a detergent respectively to obtain a treated bottom electrode layer; S2) diluting the hole transport material with a diluent, spin coating the material on the bottom electrode layer after the treatment in step S1), and then annealing the material to form a hole transport layer on the bottom electrode layer after the treatment; S3) dissolving the first active material and the second active material in a first solvent, spin coating the materials on the hole transport layer in step S2), and then annealing the materials at 50-200° C. or treating the materials with the second solvent vapor at 20-50° C., thereby further preparing a light absorbing active layer on the product of step S2); The first active material is a small molecule having an absorption cutoff wavelength below 600 nm, and the second active material is a small molecule material having absorption in the near infrared region, and its absorption wavelength can be up to 800 nm-1500 nm; The solvent vapor treatment includes adding a second solvent into a glass culture dish until the vapor is saturated, then placing the spin-coated active layer film on the back of another blank culture dish cover, and quickly exchanging the culture dish cover on which the active layer film is placed with the culture dish cover containing the saturated vapor of the second solvent, and after 0 seconds to 300 seconds, taking out the film from the culture dish to obtain a light-absorbing active layer; S4) spin coating an electron transport material on the product of step S3), thereby further preparing an electron transport layer on the product of step S3); S5) Using PDMS, the top electrode is transferred onto the electron transport layer obtained in step S4) to produce a solar cell.
2. The method according to claim 1, wherein: The bottom electrode is selected from an ITO bottom electrode, a FTO bottom electrode, an AZO bottom electrode, AgNW or a carbon electrode.
3. The method according to claim 1, wherein: The hole transport material is selected from one or more mixed materials of PEDOT:PSS, MoO3, CuI, CuPc, ZnPc, TiOPc, PF8-TAA, PIF8-PTAA, PTAA, PTB7, Alq3, CuSCN, PFO, CuInS2, NiOx, WOx, Spiro-OMeTAD.
4. The method according to claim 1, wherein: The first active material is TPD-2TPA, and the second active material is Y6.
5. The method according to claim 1, wherein: The first solvent used in step S3) is selected from chloroform, chlorobenzene (CB), and toluene; the second solvent is selected from chloroform, THF, CB, CS2 and toluene; the concentration of the first solvent is 10-25 mg / mL; the concentration of the second solvent is such that it is vapor saturated in the culture dish; the mass ratio of the first active material to the second active material is 1:4 to 4:1; the annealing temperature is 130-150° C.; and an active layer additive is optionally further added, the active layer additive being 0.5%-3% by volume of chloronaphthalene.
6. The method according to claim 1, wherein: The electron transport material is selected from one or a mixed material of more than one of PDINO, BCP, ZnO, MgO, SnO2, TiO2, ZrO2, Nb2O3, Al2O3, PEIE, PFN-Br, PFSO3Na, PFN / PFBT, and Alq3.
7. The method according to claim 1, wherein: The positions of the electron transport layer and the hole transport layer can be interchanged.
8. The method according to claim 1, wherein: The top electrode is selected from one or more mixed materials of PH1000:AgNWs, PH1000, AgNWs, CuNWs, ITO, carbon nanotubes, graphene, etc.
9. The method according to claim 1, wherein: The solar cell is an opaque or transparent solar cell.
10. The method according to claim 1, wherein: The solar cell is a flexible transparent solar cell.
11. A solar cell prepared according to the method of any one of claims 1 to 10.